Pengukuran Tingkat Pengetahuan Tentang Bahaya Keselamatan Sebelum Dan Sesudah Edukasi Pada Siswa/I Sekolah Dasar X Depok - Yusvita, Fierdania; Desyawati Utami (Public Health Study Program, Faculty of Health Science, State Islamic University (UIN) Syarif Hidayatullah Jakarta, Indonesia., 2025)
Schools have various safety hazards due to their teaching and learning activities. These hazards can cause losses such as injuries, health problems, and damage to school property and the environment. This study aims to determine the effect of safety education on students' knowledge levels. A pre-experimental design with a one-group pretest-posttest was used for the research design. A total of 32 respondents, including student representatives, Junior Doctors, and Scouts from SD X in Mekarjaya, Kota Depok, West Java, participated in the study. The study was conducted in October 2024. Safety education was delivered through lectures, posters, and PowerPoint presentations. Knowledge improvement was measured by distributing questionnaires about safety hazards and risks at school before and after the educational program. The analysis was conducted using a t-test. The results showed that the average score was 50.84 before the educational program and increased to 89.22 after. These results indicate a significant improvement in knowledge of safety hazards at school (p-value = 0.000). It is recommended that SDN Mekarjaya 11 Depok's management conduct regular health and safety education activities involving all stakeholders, including parents and the local education office, to optimize the development of a safety culture at the school. Keywords : Safety Hazard, Safety at School, Safety Promotion